Formulation and Characteristic Test of Solid Soap From Ethanol Extract of Papaya Seeds (Carica papaya L.) - Leny, Leny; Fransiska, Ella; Nababan, Herbet; Hafiz, Ihsanul; Iskandar, Benni (Media Kesehatan Politeknik Kesehatan Makassar, 2021)
The large consumption of papaya in Indonesia causes the availability of papaya seeds to be abundant and has not been used wisely. Papaya seeds contain secondary metabolites such as phenols, terpenoids, alkaloids and saponins which have an antibacterial activity. The purpose of this study was to develop papaya seeds into a cosmetic form and in this study is to formulate it into solid soap. The research was initiated by making an extract which was then formulated into solid soap with various concentrations of 2%, 4%, and 6%. Soap is tested for its characteristics to meet the requirements of soap in SNI 06-3532-1994. The soap meets the criteria for the pH requirement, which is between 9-10, has a water content of 1%, free alkali content of 0.044%, forms a stable foam and does not change during storage by using cycling test method.